AN ANALYSIS OF STUDENTS’ SKILL IN WRITING BUSINESS LETTER AT THE FIVE SEMESTER UNIVERSITY OF PASIR PENGARAIAN - Pipit Rahayu; Eripuddin Eripuddin; Ikhwan Dwi Kurniawan; Azi Nurazima Juhastri (JEE (Journal of English Education), 2025)
The purpose of this research is to see how the ability to write business letters of five semester English language students at Pasir Pengaraian University is. The data analysis method that researchers use is a writing test. English language students of University provide writing test results, the researcher found that students' skills in writing business letters were quite good based on the results of three raters' assessment data. Considering the findings of the previous chapter, data fraud, and data analysis, the researcher concluded that eleven of the twenty- one students had fairly good skills in writing business letters and the rest low. Moderate and high criteria.The conclusion of this research is on the content indicator, three students obtained a perfect score of 3.00 from three rater, although there are students who achieve average is 2.33 with moderate criteria. Organizational indicators show similar variations with 2.33 moderate content indicators. And language 3 students received score of average is 2.36 with high criteria.